Consumers willingness to pay for organic beef: Evidence from Dhaka City - Sarma, PK; Raha, SK (Journal of the Bangladesh Agricultural University, 2016)
This study was carried out in order to identify consumers willingness to pay a price premium for organic beef in Dhaka city of Bangladesh during the period July-December 2015. The research surveyed 180 consumers using semistructured questionnaires to examine consumers perception about organic beef and assess their willingness to pay for beef. The study revealed that all respondents are willing to pay price premium for organic beef. Consumers are willing to purchase organic beef because these beef are free of pesticides, chemical, drug, steroid, etc. A health conscious is one of the main determinants of willing to pay followed by consumer perception and quality towards the organic beef. A total of 41% of the consumers are willing to pay 0-5% price premium, whereas 30% are willing to pay up to 10% price premium. About 19% of the respondents feel the extra cost for organic beef is reasonable, while 10% considered it too high. The survey also suggested that the consumption of organic beef is increasing; however, develop production method, slaughtering process, processing, packaging, labeling, and innovations hallal certification from Islamic foundation are needed to stimulate further demand. It was also found that only some groups of consumers are willing to pay the premium necessary for alternative methods of production. J. Bangladesh Agril. Univ. 14(1): 83-91, June 2016